Determinants of Gender Differences in Change in Pay among Job-Switching Executives. (January 2022) - Groysberg, Boris; Healy, Paul; Lin, Eric
The authors investigate what determines differences in change in pay between men and women executives who move to new employers. Using proprietary data of 2, 034 executive placements from a global search firm, the authors observe narrower pay differences between men and women after job moves. The unconditional gap shrinks from 21.5% in the prior employer to 15% in the new employer. After controlling for typical explanatory factors, the residual gap falls by almost 30%, from 8.5% at the prior employer to 6.1% in the new placement. This change reflects a relative increase in performance-based compensation for women and a lower level of unexplained pay inequality generally in external placements. Controlling for individual fixed effects, observed women have higher pay raises than do men. Finally, the authors find suggestive evidence that pay differences may also be moderated by differences in the supply and demand for women executives.